Preparation and controlled release properties of zinc-layered hydroxides-cinnamaldehyde and gellan gum cinnamaldehyde hydrogel beads - Jamaluddin, Nurul Jannah (2017)
Mosquitoes are giving threat and responsible for the transmission of many deadly diseases such as malaria, dengue, chikungunya and the latest outbreak disease, the zika virus. Insecticides and larvicides are one of the solutions to lower down the mosquitoes population but most of the products in the current market are synthetic and are not environmental friendly. Cinnamaldehyde (CN) is the main constituent of cinnamon oils has been reported to possess excellent inhibitory effects in killing mosquito larvaes. Looking at the interesting properties of CN, has brought the idea to intercalate and encapsulate CN into two different nano host materials; zinc layered hydroxides (ZLH) and gellan gum hydrogel. The two hosts are chosen due to their eco-friendly material, low cost and easy to prepare. Controlled release study is better than using the anion directly as the hosts will protect the anions and the anions can be release in sustained and longer time. Intercalation of CN into ZLH was done via ion exchange method forming the zinc-layered hydroxides-cinnamaldehyde (ZCN) nanocomposites. X-ray diffraction pattern indicated a successful intercalation of CN into the interlayer galleries of ZLHs matrix when 1g of ZnO with 0.08M concentration of CN was used. Considering with the X-Ray diffraction and FTIR analyses, successful formation of ZCN was further confirmed. Further physico-chemical characterisations of the resulting materials including thermal analysis, elemental analysis and surface morphology, were also carried out. Encapsulation of cinnamaldehyde into gellan gum hydrogel was done via ionotropic gelation method forming gellan gum cinnamaldehyde hydrogel beads (CNB). FTIR analysis shows that functional groups of both CN and gellan gum appeared in all CNB (cinnamaldehyde concentrations 0.01M to 0.32M). The samples were then further characterised by elemental analysis and surface morphology analysis. The swelling study of CNB was done in tap water and lake water which are the common breeding media for mosquito larvae. As CN concentration increases, the swelling percentage decreases ranging 544% to 484% for tap water (pH 6.7) and 628% to 544% for lake water (pH 7). In the degradation study, CNB were exposed at room temperature until day 8 and showed decrease in weight percentage. The controlled release study of CN was done in three media that resemble the mosquito breeding condition which are tap water (pH 6.7), MARDI lake water (pH 7.0) and Sri Serdang lake water (pH 7.5). Controlled release of CN from both ZCN and CNB was rapid intially and slow thereafter. The release percentage of CN into the media for both ZCN and CNB can be arranged in the order of pH 7.0 > pH 7.5 > pH 6.7. The highest release percentage recorded was 90.7% for ZCN while 70.4% for CNB. It was found that the release is slow and highly in sustained manner over 40 hours. The kinetic model of pseudo-second order fits well with most of the release profile with r2 > 0.9 for both ZCN and CNB. Two new host-anion materials has been successfully prepared. This highlighted the potential of both hosts that can be prepared using simple, direct reaction of CN and two hosts; gellan gum and ZLH in the application of controlled release formulations for mosquito control.